THE INFLUENCE OF ACADEMIC SUPERVISION AND SCHOOL CULTURE ON TEACHER'S PEDAGOGIC COMPETENCY IN DEMAK DISTRICT - Wakhidatun Niswah; Su'ad Su'ad; Sri Utaminingsih (Universitas Muria Kudus, 2021)
This study aims to analyze how much influence the principal's academic supervision and school culture have on the pedagogical competence of elementary school teachers in Demak Regency. This research uses quantitative research methods, the research sample includes 114 elementary school teachers at 41 public elementary schools in Wonosalam District, Demak Regency. Data collection techniques using questionnaires and documentation. The sampling technique used purposive sampling technique with a type of simple random sampling. The data analysis technique uses correlation data analysis techniques, multiple linear regression. The results showed that the principal's academic supervision and school culture influenced the pedagogical competence of elementary school teachers as much as 42.7%. The conclusion of this study is that there is an effect of the principal's academic supervision and school culture on the pedagogical competence of elementary school teachers.